The Effectiveness of Recess Activities for Members of the Pandeglang DPRD in Absorbing Proposed Infrastructure Development Programs: Study in Dapil 2, Pandeglang Regency, Banten Province - Hasanudin Hasanudin; Ipah Ema Jumiati; Julianes Cadith (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
The purpose of the study was to determine how much effectiveness the recess activities of members of the Pandeglang DPRD in absorbing the proposed infrastructure development program in Dapil 2 Pandeglang Regency. The theory of effectiveness according to Gibson, Donnely and Ivancevich includes production, efficiency, satisfaction, adaptation and development. The research method uses quantitative methods with a descriptive design. The population of the study was the people who were recorded as the Permanent Voters List for the Pandeglang District 2 in the general election for the 2019-2014 period with a total of 136,443 people. The sampling technique used proportionate stratified random sampling with as many as 400 respondents. Data analysis used SPSS Version 23 program. The results of the study found that the effectiveness of the recess activities of members of the Pandeglang DPRDin Dapil 2 was declared effective. This was obtained from the hypothesis testing criteria which obtained a value of tcount > ttable (56.282 > 1.649), then H0 was rejected and Ha was accepted. The percentage of effectiveness of recess activities for members of DPRD Pandeglang Dapil 2 is 69.94%.